Path-dependent bond-line evolution in equilibrated core honeycomb sandwich structures - Daniel Zebrine (Taylor & Francis Group, 2020)
During co-cure of honeycomb core sandwich panels, composite facesheets are cured and concurrently bonded to the core, introducing complex interactions that can lead to unsatisfactory bond-line formation. In this work, an in situ co-cure fixture is employed to directly observe the adhesive during processing and identify defect formation mechanisms specific to the bond-line. Relating fillet quality to imposed core pressure reveals the non-linear effect of core pressure. High pressures suppressed voids; intermediate pressures resulted in void growth and entrapment within deformed fillets; and low pressures led to void rupture and small, irregular fillets. Experimental results aided in developing a model to predict void growth in the bond-line. The findings presented here provide insight into the physics controlling the adhesive bond-line evolution during co-cure, which can inform manufacturing decisions to produce higher-quality honeycomb core sandwich structures.